Strategi Pengelolaan Konten Komunikasi Pemasaran Digital Berbasis Islam Melalui Media Sosial Instagram - Farah Nur Fadillah; Raditya Pratama Putra (Bandung Conference Series: Communication Management, 2023)
Abstract. This research was motivated by Halalpedia's uniqueness in conducting digital marketing communication strategies in creating content on Instagram social media based on Islamic values. This study aims to find out the content of Islamic value-based marketing communication through Instagram carried out by Halalpedia, the company's engagement strategy through Islamic value-based marketing content on Instagram and to find out the reasons for the application of Islamic values in Halalpedia content on Instagram. This research uses qualitative methods with a case study approach. The data collection techniques in this study are interviews, observations and documentation. The subjects of the study were conducted on social media specialists, direct marketing, marketing communication. The subjects of the study were conducted on social media specialists, direct marketing, marketing communication. The analysis techniques used are data reduction, display data, conclusion drawing. As a companion to this research process. The theory used is the theory used in this study, namely the POAC theory from George R Kelly (1999) which assumes that a company needs to be managed in order to run and develop properly, it needs governance which includes planning, organizing, leadership and supervision and the process of content marketing model, this model assumes that content marketing includes planning of goals, strategy of content compilation, distribution and improvement of content and supply chain of content. The results of this study are 1) Halalpedia marketing communication content contains an explanation of the content inserted Islamic values that are not discussed in depth so that the segmentation is general. 2). Engagement strategies by applying Islamic values are effective because there is always an increase both in terms of interaction and increasing the number of followers. 3). The reason Halalpedia applies Islamic values to its content is to attract awareness from Instagram users, because Halalpedia sees that the population in Indonesia is the largest adherent of Islam and also the most popular social media in Indonesia, namely Instagram. Abstrak. Penelitian ini dilatarbelakangi oleh keunikan Halalpedia dalam melakukan stategi komunikasi pemasaran digital dalam membuat konten di media sosial Instagram berbasis nilai islam. Pada penelitian ini memiliki tujuan untuk mengetahui konten komunikasi pemasaran berbasis nilai islam melalui Instagram yang dilakukan oleh Halalpedia, strategi engagement perusahaan melalui konten pemasaran berbasis nilai islam di Instagram dan untuk mengetahui alasan penerapan nilai Islam dalam konten Halalpedia di Instagram. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Adapun teknik pengumpulan data pada penelitian ini yaitu wawancara, observasi dan dokumentasi. Subjek penelitian dilakukan pada sosial media specialist, direct marketing, marketing communication. Teknik analisis yang digunakan yaitu data reduction, display data, conclusion drawing. Sebagai pendamping dari proses penelitian ini. Adapun teori yang digunakan yaitu teori yang digunakan pada penelitian ini yaitu teori POAC dari George R kelly (1999) yang mengasumsikan bahwa suatu perusahaan perlu dikelola agar dapat berjalan dan berkembang dengan baik, perlu tata Kelola yang meliputi perencanaan, pengorganisasian, kepemimpinan dan pengawasan dan model process of content marketing, model ini mengasumsikan bahwa konten pemasaran meliputi planning of goals, strategy of content compilation, distribution and improvement of content dan supply chain of content. Hasil dari penelitian ini yaitu 1).konten komunikasi pemasaran Halalpedia berisi penjelasan pada konten diselipkan nilai islam yang tidak dibahas secara mendalam agar segmentasinyageneral. 2). Strategi engagement dengan menerapan nilai islam merupakan hal yang efektif karena selalu ada peningkatan baik dari segi interaksi maupun penambahan jumlah followers. 3). Alasan Halalpedia menerapkan nilai islam pada kontennya yaitu untuk menarik awareness dari pengguna instagram, karena Halalpedia melihat bahwa penduduk di indonesia merupakan pemeluk agama islam terbanyak dan juga media sosial yang paling banyak diminati di indonesia yaitu Instagram.